Overexpression of mGluR7 in the Prefrontal Cortex Attenuates Autistic Behaviors in Mice - Wang, Xiaona; Gao, Chao; Zhang, Yaodong; Hu, Shunan; Qiao, Yidan; Zhao, Zhengqin; Gou, Lingshan; Song, Jijun; Wang, Qi (Frontiers in Cellular Neuroscience, 2021)
Autism spectrum disorder (ASD) is associated with a range of abnormalities pertaining to socialization, communication, repetitive behaviors, and restricted interests. Owing to its complexity, the etiology of ASD remains incompletely understood. The presynaptic G protein-coupled glutamate receptor metabotropic glutamate receptor 7 (mGluR7) is known to be essential for synaptic transmission and is also tightly linked with ASD incidence. Herein, we report that prefrontal cortex (PFC) mGluR7 protein levels were decreased in C57BL/6J mice exposed to valproic acid (VPA) and BTBR T+ Itpr3tf/J mice. The overexpression of mGluR7 in the PFC of these mice using a lentiviral vector was sufficient to reduce the severity of ASD-like behavioral patterns such that animals exhibited decreases in abnormal social interactions and communication, anxiety-like, and stereotyped/repetitive behaviors. Intriguingly, patch-clamp recordings revealed that the overexpression of mGluR7 suppressed neuronal excitability by inhibiting action potential discharge frequencies, together with enhanced action potential threshold and increased rheobase. These data offer a scientific basis for the additional study of mGluR7 as a promising therapeutic target in ASD and related neurodevelopmental disorders.